Affiliate Marketing terhadap Minat Beli Mahasiswa di TikTok Shop - Brilianita, Setia; Sulistyowati, Raya (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2023)
The growth of the internet has transformed the function of social media as a platform to deliver attention-grabbing marketing communications. The digitalization of media has made affiliate marketing emerge as a popular marketing strategy amidst the growth of social media nowadays. The influence of social media such as TikTok offers a new way of shopping online through affiliate marketing. Thus, this study aims to find the effect of affiliate marketing on students' purchase intention at TikTok Shop. This research uses a quantitative approach with an explanatory type. The population in this study were students of the Faculty of Economics and Business, Surabaya State University with a total of 290 respondents obtained through purposive sampling. The data analysis technique was carried out using a Structural Equation Modeling approach with Partial Least Squares (SEM-PLS) assisted by SmartPLS 3.0 software. This study found that affiliate marketing has a positive and significant effect on students' purchase intention at TikTok Shop. Affiliate marketing at TikTok makes consumers tend to feel more confident and trust in products that are supported by a strong and trusted affiliate program.